FROST INVESTIGATION 1944-1945. APPENDIX 3. REPORT ON OTIS FIELD, SANDWICH, MASSACHUSETTS. APPENDIX 4. REPORT ON HOULTON AIRFIELD, HOULTON, MAINE. - ARCTIC CONSTRUCTION AND FROST EFFECTS LAB BOSTON MASS (1945)
The report presents the results of the frost investigation conducted at Otis Field, Sandwich, Massachusetts and Houlton Airfield, Houlton, Maine during the period from November 1944 through May 1945. The investigation includes test areas in which observations were made of frost penetration, ice segregation, water content, and density. In place C. B. R. tests were made on the subgrade soil. Atterberg limits and mechanical analysis tests were performed on representative samples. The climatic and other general conditions related to the frost investigation also are included in this report. (Author) See also Appendix 2, AD-712 382 and Appendix 5, AD-712 383.